2016
DOI: 10.4236/ojf.2016.62010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Appropriate Identification of Deforestation Agents and Drivers for Designing REDD+ Readiness Activities through an Examination of the Area around Gunung Palung National Park, Indonesia

Abstract: For effective REDD+ implementation with multiple readiness activities, agents and drivers of deforestation and forest degradation needs to be identified appropriately. This study examined how such identification can be utilized for instituting REDD+ activities design. We examined this question by using satellite imagery analysis and socioeconomic surveying around Gunung Palung National Park in Indonesia. After recognizing the deforestation rate in the area, the characteristics of agents and drivers of deforest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…(1) the characteristics of each ethnic group were confirmed by comparing assets (possession of livestock and land-use rights) and income sources; (2) a CDA was used to clarify the variables that separated each ethnic group; and (3) a PCA was used to capture the current status of the community, visualize the distribution of land-use rights and assess the value given to cooperation within the community. According to previous research [23,29], a CDA is useful for identifying the important factors that characterize multiple types of objects, such as ethnic groups, while a PCA can be used to visually understand the community's characteristics by reducing the number of socioeconomic factors [29,30]. For the CDA, we assumed multivariate normality and confirmed that our data were not highly correlated (<0.7).…”
Section: Discussionsupporting
confidence: 54%
“…(1) the characteristics of each ethnic group were confirmed by comparing assets (possession of livestock and land-use rights) and income sources; (2) a CDA was used to clarify the variables that separated each ethnic group; and (3) a PCA was used to capture the current status of the community, visualize the distribution of land-use rights and assess the value given to cooperation within the community. According to previous research [23,29], a CDA is useful for identifying the important factors that characterize multiple types of objects, such as ethnic groups, while a PCA can be used to visually understand the community's characteristics by reducing the number of socioeconomic factors [29,30]. For the CDA, we assumed multivariate normality and confirmed that our data were not highly correlated (<0.7).…”
Section: Discussionsupporting
confidence: 54%
“…To develop an effective REDD+ intervention, it is essential to address the causes of deforestation and forest degradation (Hosonuma et al, 2012;Minang et al, 2014;Moonen et al, 2016). Understanding and linking direct and indirect drivers to policy development and implementation is critical (Goetz et al, 2014;Tegegne et al, 2016;Yoshikura et al, 2016) to modify recent trends in forestry leading towards better climate future.…”
Section: Deforestation and Forest Degradationmentioning
confidence: 99%
“…Ghana is one of the several developing countries encouraged to reduce forest losses for reducing emissions from deforestation and forest degradation, conservation, and enhancement of carbon stocks (REDD+) benefits [10]. e development of national strategies and action plans for REDD+ in 46 developing countries has shown that commercial and subsistence agriculture is the main instigator of forest loss, whilst unsustainable logging is identified as another major degradation enhancer [11].…”
Section: Introductionmentioning
confidence: 99%